Chapter 5 English-Medium Instruction in Emirati Higher Education The Importance of Choice and Agency - Hopkyns, Sarah (Taylor & Francis, 2023)
This chapter begins by providing an overview of the many educational reforms which have taken place in the United Arab Emirates within its short history as a nation. Pushed forward by neoliberalism and globalisation, such reforms have largely focused on increasing amounts of English-medium instruction at all levels of education. In the United Arab Emirates, not only does English dominate teaching and learning, but its 'de facto lingua franca' status in public domains has led to heated debates centred around the effects of 'Englishisation' on the Arabic language, as well as its impact on local cultural identities. The chapter discusses the concept of agency with reference to student and teacher roles in English-medium instruction settings. Specifically, the sociolinguistic implications of English-medium instruction for Arabic-speaking university students are explored. It is argued that often structural constraints such as 'English only' classroom policies reinforce monolingual ideologies, with English also acting as a gatekeeper to academic success, so that naturally occurring translingual practice is deprecated. Referencing previous research, the chapter will conclude by advocating the need for increased choice and agency surrounding English-medium instruction in order for educational experiences to be empowering rather than subtractive.